Teresita de Barbieri. Mujeres y vida cotidiana. México : SEP/FCE, 1984. (Col. Sep 80 ; no. 60) - Muñoz Contreras, María Elena (Estudios Demográficos y Urbanos, 1986)
TERESITA DE BARBIERI. Mujeres y vida cotidiana, SEP/FCE, México, 1984.